The Effect of Vertical Loads and the Pile Shape on Pile Group Response under Lateral Two-Way Cyclic Loading - Aseel Kahlan Mahmood; Jasim M Abbas (Civil Engineering Journal, 2019)
This paper is presented the lateral dynamic response of pile groups embedded in dry sand under influence of vertical loads and the pile shape in-group, which are subjected to the lateral two-way cyclic loads. The laboratory typical tests with pile groups (2×1) have an aluminum-pipe (i.e. circular, square) pile, embedded length to diameter of pile ratio (L/D=40) and spacing to diameter ratio (S/D) of 3, 5, 7 and 9 are used with different cyclic-load ratio (CLR) 0.4, 0.6 and 0.8. The experimental results are revealed that both the vertical and lateral pile capacity and displacement is significantly affected by the cyclic-loading factors i.e. (number of cycles, cyclic load ratio, and shape of pile) .In this study, important design references are presented. Which are explained that the response of the pile groups under cyclic lateral loading are clear affected by the attendance of vertical load and pile shape. Where, it is reduction the lateral displacement of group piles head and increase lateral capacity about (50) % compared without vertical loads. On the other side, the pile shape is a well affected to the pile response where the level of decline in lateral displacement at the pile groups head in the square pile is more than circular pile about 20 % at the same load intensity.